Let's catch octopus for dinner: ancient inventions of octopus lures in the Mariana Islands of the remote tropical pacific. Issue 4 (8th August 2021) - Carson, Mike T.; Hung, Hsiao-chun
ABSTRACT: When people first lived in remote tropical seashores, they developed novel adaptations for living in these extreme environments, including the use of a specialized octopus lure device. The evidence for this fishing tradition now can be traced back as early as 1500–1100 BC in the Mariana Islands of Western Micronesia. New research has examined the artefacts of these compound lure devices, especially concerning the cut and drilled dorsum pieces of cowrie ( Cypraea spp.) shells. Without this archaeological evidence, octopuses would have been undetected in the ancient deposits, and therefore a significant portion of past diet, innovative technology, and traditional practice would have been hidden from modern knowledge. The findings portray a broader and more realistic scene of ancient coastal communities, with implications beyond the confines of the specific island societies of the Pacific.